APLIKASI FORECASTING DALAM MENGESTIMASI PENJUALAN PRODUK DI MASA MENDATANG - Muhammad Isa (Institut Agama Islam Negeri Padngsidimpuan, 2015)
Forecasting is the effort to predict what will be happen in the future. Forecastingalso applied to estimate the selling volume of our product. There are many typesof forecasting methods. One of them is “trend method”. This type is easy andpractise to used. It began with finding the trend equations (linier, parabolic, andexponential)then examine the trend equations to know their error levels. Thetrend equation with minimum error is the best formula to predict the sellingvolume of our product in the future.